ANALISIS YURIDIS PROSEDUR PEMBATALAN HIBAH TERHADAP TANAH YANG SUDAH DIBALIKNAMAKAN OLEH PENERIMA HIBAH (PUTUSAN PA MALANG NO.1000K/PDT.G/2011/PA.Mlg) - MOHD SOFYAN ASSAURI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. H.M. Hasballah Thaib, MA, PhD2. Dr. Utary Maharany Barus, SH, MHum3. Dr. Yefrizawati, SH, MHum Article 1666 of the Civil Code states that Grant is “an agreement in which a grantor gives an object that is complimentary and cannot be taken back for the benefit of the grantee. The plaintiffs mention, in the civil lawsuit filed in Malang Religious Court No. 1000k/pdt.g/2011/pa.mlg, that the defendant has forcefully and without any notice granted their other child a piece of land which title is directly transferred afterwards.The results of theresearch demonstrate that the lawsuit filed by the plaintiffss is caused by themselves , in this case parents, do not know that the the deed they have signed is a deed of grant, in which it states the grant of a certified land. The judge objects the plaintiffs’ lawsuit because the deed made by the Notary contains statement that any dispute in the future shall be settled by the District Court.Keywords: Grant Cancellation, Transferred Land Title, Grant